Systematic Review of Pharmacological Properties of the Oligodendrocyte Lineage - Marinelli, Carla; Bertalot, Thomas; Zusso, Morena; Skaper, Stephen D.; Giusti, Pietro (Frontiers in Cellular Neuroscience, 2016)
OOligodendrogenesis and oligodendrocyte precursor maturation are essential processes during the course of central nervous system development, and lead to the myelination of axons. Cells of the oligodendrocyte lineage are generated in the germinal zone from migratory bipolar oligodendrocyte precursor cells, and acquire cell surface markers as they mature and respond specifically to factors which regulate proliferation, migration, differentiation, and survival. Loss of myelin underlies a wide range of neurological disorders, some of an autoimmune nature – multiple sclerosis probably being the most prominent. Current therapies are based on the use of immunomodulatory agents which are likely to promote myelin repair (remyelination) indirectly by subverting the inflammatory response, aspects of which impair the differentiation of oligodendrocyte precursor cells. Cells of the oligodendrocyte lineage express and are capable of responding to a diverse array of ligand-receptor pairs, including neurotransmitters and nuclear receptors such as gamma-aminobutyric acid, glutamate, ATP, serotonin, acetylcholine, nitric oxide, opioids, prostaglandins, prolactin, cannabinoids and nuclear receptors. The intent of this review is to provide the reader with a synopsis of our present state of knowledge concerning the pharmacological properties of the oligodendrocyte lineage, with particular attention to these receptor-ligand (i.e., neurotransmitters and nuclear receptor) interactions that can influence oligodendrocyte migration, proliferation, differentiation, and myelination, and an appraisal of their therapeutic potential. For example, many promising mediators work through Ca2+ signalling, and the balance between Ca2+ influx and efflux can determine the temporal and spatial properties of oligodendrocytes. Moreover, Ca2+ signalling in oligodendrocyte precursor cells can influence not only differentiation and myelination, but also process extension and migration, as well as cell death in mature mouse oligodendrocytes. There is also evidence that oligodendroglia exhibit Ca2+ transients in response to electrical activity of axons for activity-dependent myelination. Cholinergic antagonists, as well as endocannabinoid-related lipid-signalling molecules target oligodendrocytes. An understanding of such pharmacological pathways may thus lay the foundation to allow its leverage for therapeutic benefit in diseases of demyelination.